Higher cancer antigen 125 level is associated with the presence of permanent atrial fibrillation in systolic heart failure patients. Issue 1 (1st February 2016) - Kaya, Hakki; Zorlu, Ali; Yucel, Hasan; Tatlisu, Mustafa Adem; Kivrak, Tarik; Coskun, Abuzer; Yilmaz, Mehmet Birhan
Abstract : Introduction Atrial fibrillation (AF) is a common arrhythmia in heart failure (HF). Recent studies have shown that serum cancer antigen-125 (CA-125) levels are elevated in HF, and high levels of CA-125 in HF patients with sinus rhythm have been shown to be associated with the development of new onset AF. However, the relation between CA-125 levels and the presence of AF in HF is unknown. In this study we investigated whether plasma CA-125 levels in patients with systolic HF could predict the presence of AF. Methods The study was a retrospective cohort design including 205 stable systolic HF patients who were selected during outpatient clinic visits and who had CA-125 measurement and an electrocardiogram within the last one month before admittance to cardiology clinic. Patients were classified into two groups based on the presence of AF (n = 67) or sinus rhythm (n = 138). Results The mean age of the patients was 68 ± 11 years. CA-125 levels were significantly higher in patients with AF than patients with SR [33 (3-273) vs 102 (7-296) U/ml, P < 0.001]. CA-125 level, presence of right ventricular dilatation, pericardial effusion, moderate to severe TR and MR, and left atrial diameter were found to be associated with the presence of AF in univariate analysis. In a multivariate logistic regression model, only the CA-125 level remained associated. Also, according to the ROC curve analysis, the optimal cut-off level of CA-125 for predicting AF was ≥ 91 U/mL with a specificity of 84% and a sensitivity of 54%. Conclusion We have shown that the CA-125 levels can be used to predict AF in patients with systolic HF.